Electrocoalescence behavior of two identical droplets with various droplet radii. (25th January 2017) - Wang, Bing-Bing; Wang, Xiao-Dong; Wang, Tian-Hu; Yan, Wei-Mon
Abstract: In electric dehydration of crude oil, electrocoalescence of water droplets can be remarkably enhanced by increasing electric field strength, which promotes the settling separation of water droplets. However, non-coalescence of droplets occurs when the electric strength is higher than a critical value ( E c ). Smaller daughter droplets will be ejected from the coalescing droplet in the process of the non-coalescence, which is undesirable for separation of droplets from crude oil. This work simulates the electrocoalescence of two identical droplets with dissolved KCl via molecular dynamics method. The results show that the value of E c decreases with the increase of the droplet radius, this is because daughter droplets can be ejected more easily from the coalescing droplet with a larger radius due to stronger electric field force and smaller interfacial force. With the same initial centroid distances, the attractive energy between two larger droplets is stronger when an electric field is applied, and hence the two droplets migrate towards one another faster. However, the merging rate of the coalescing droplet is higher after two smaller droplets come into contact. In addition, it is also found that the daughter droplet with dissolved K + is more easily ejected from the coalescing droplet during the non-coalescence, as compared to the daughter droplet with dissolved Cl − .